Historic and Commemorative Function of Street Names in the Linguistic Landscape: cases of Rumšiškės and Šlienava - Šidlauskas, Žydrūnas (Respectus Philologicus, 2026)
The article analyses localism in street naming practices. Drawing on a quantitative method previously tested in Kaunas district, it identifies the most locally specific street names in Rumšiškės (Kaišiadorys district) and Šlienava (Kaunas district) – those serving informational and symbolic functions. The two localities form part of the Nemunas valley, areas that were flooded during the construction of the Kaunas Hydroelectric Power Plant. Street names reflecting this past are strongly local in orientation, commemorating the rupture caused by relocation, are embedded in cultural memory, and almost become memorials themselves. On this basis, the article distinguishes informational, symbolic, identity, cultural memory, and commemorative functions of street names. The locally salient names analysed, reflecting surnames of notable local inhabitants, names of local geographical features, and names of nearby (existing or extinct) villages, demonstrate that both areas are part of a historical memory and sustain an ongoing connection to it. This connection is stronger in Rumšiškės, related to its status and the deliberate representation of the town, which was relocated from the bottom of the Kaunas Lagoon.